1994
DOI: 10.1093/carcin/15.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Ni3S2 specifically enhances the formation of oxidants in the nuclei of CHO cells as detected by dichlorofluorescein

Abstract: Dichlorofluorescein (DCF) was used as a fluorescent probe to detect oxidants formed in cultured CHO cells during nickel treatment. Crystalline Ni3S2 specifically enhanced the formation of oxidants in the nuclei of these living cells, but Ni3S2 particles did not enhance DCF fluorescence as much when added in vitro to isolated nuclei. Our results add to the emerging concept that oxidants mediated by nickel compounds may play an important role in nickel-induced genotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Soluble and insoluble nickel compounds both produce ROS in cells [181,182]. The oxidative effects of nickel depend on its ability to form the Ni(III)/Ni(II) redox couple around pH 7.4.…”
Section: Mediation Of Oxidative Damagementioning
confidence: 99%
“…Soluble and insoluble nickel compounds both produce ROS in cells [181,182]. The oxidative effects of nickel depend on its ability to form the Ni(III)/Ni(II) redox couple around pH 7.4.…”
Section: Mediation Of Oxidative Damagementioning
confidence: 99%
“…Nickel induces rather weak oxidative stress that depletes glutathione and activates nuclear factor kappa B (NF-κB) and other oxidatively sensitive transcription factors (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…The assay employed has been used for detection of H202 as a measure of nickel-induced oxidative stress in CHO cells (Huang et al 1993(Huang et al , 1994. In our previous study (17), it has been found that the conversion of non-fluorescent CDFH reducing substrate into measureable fluorescent oxidized CDF exhibited a dose-dependent requirement for peroxidase, H202 or organic hydroperoxides.…”
Section: Discussionmentioning
confidence: 99%
“…Nickel has been shown to cause inactivation of certain genes (Klein et al 1991, Salnikow et al 1994, as well as induction of oxidative stress (Huang et al 1993(Huang et al , 1994. Switching off expression of peroxidase would render cells more resistant to nickel-induced oxidative stress injury, resulting in positive selection of those cells.…”
Section: Discussionmentioning
confidence: 99%